Promissory estoppel under contract law: it’s application in Malaysia / Iznan Ishak - Ishak, Iznan (Faculty of Law, 1987)
1. The law of contract can be described on that branch of the law which determines the circumstances in which a promise shall be legally binding on tile person making it. A contract is also an agreement enforceable at law. Contract is a species off an agreement whereby a legal obligation is constituted and define between the parties to it. In the American Renstatement of the law of contract defines a contract as a promise or set of promises for the breach of which the law gives a remedy, or the performance of which the law in some way recognises it as a duty. 2 The word 'contract' in a legal sense, is an agreement that is legally binding between the parties as stated under section 2(b) Malaysian Contract Act 1950."An agreement enforceabIe by law is a contract" Thus, all contracts must be built upon an agreement although not all agreements are automatically contracts. Most contracts take the form of an agreement, that is each party agrees to accept the promise or promises made by himself.